• Упростите выражение
    1) (2х – 5)(3х + 4)
    2) (х – 3у)(2у – 5х)
    3) а(а – 5) – (а - 2)(а - 3)
    4) (2с + 1)(4с2 – 2а + 1)
    5) А(а + 4) +(а - 2)(а + 6)

Ответы 1

  • 1)(2x - 5)(3x + 4) = \\ 6x { }^{2} + 8x - 15x - 20 = \\ 6 x{}^{2} - 7x - 20 \\ \\ 2) \: (x - 3y)(2y - 5x) = \\ 2xy - 5x{}^{2} - 6y {}^{2} + 15xy = \\ 17xy - 5x {}^{2} - 6y {}^{2} \\ \\ 3) \: а(а - 5) - (а - 2)(а - 3) = \\ а {}^{2} - 5а - а {}^{2} + 3а + 2а - 6 = \\ - 6 \\ \\ 4)(2с + 1)(4с {}^{2} - 2а + 1) = \\ 8с {}^{3} - 4ас + 2с + 4с {}^{2} - 2а + 1 \\ \\ 5) \: а(а + 4) + (а - 2)(а + 6) = \\ а {}^{2} + 4а + а {}^{2} + 6а - 2а - 12 = \\ 2 {}^{2} + 8а - 12
    • Автор:

      claudia91
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years